Influence of Heat Accumulation in the Laser Treatment Area on the Dynamics of LIPSS Formation for Pure Titanium and Titanium Alloy - Druzhinin, Petr; Fomicheva, Iana; Amler, Hans; Leuchs, Gerd; Christiansen, Silke H. (CLEO: Applications and Technology, CLEO: A and T 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
The dependences of LSFL period and the types of large LIPSS for pure titanium and titanium alloy on the amount of heat accumulation in the treatment area by a picosecond laser are presented.
CRIS-Team Scopus Importer:2024-10-04